2020
DOI: 10.3390/dj8020036
|View full text |Cite
|
Sign up to set email alerts
|

Oral Hygiene Awareness and Practices among a Sample of Primary School Children in Rural Bangladesh

Abstract: Inadequate oral health knowledge and awareness is more likely to cause oral diseases among all age groups, including children. Reports about the oral health awareness and oral hygiene practices of children in Bangladesh are insufficient. Therefore, the objective of this study was to evaluate the oral health awareness and practices of junior school children in Mathbaria upazila of Pirojpur District, Bangladesh. The study covered 150 children aged 5 to 12 years of age from three primary schools. The study reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
7
1
3
Order By: Relevance
“…The American Dental Association (ADA) recommends that individuals brush twice per day and use floss or use other interdental cleaners once per day to effectively remove microbial plaques, which decrease caries development [ 77 ]. Similar findings were also reported in various other studies [ 33 , 46 , 78 , 79 , 80 , 81 ]. In Bangladesh, rural children are very reluctant to clean their teeth, and even if they do, they often do not use dental materials.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The American Dental Association (ADA) recommends that individuals brush twice per day and use floss or use other interdental cleaners once per day to effectively remove microbial plaques, which decrease caries development [ 77 ]. Similar findings were also reported in various other studies [ 33 , 46 , 78 , 79 , 80 , 81 ]. In Bangladesh, rural children are very reluctant to clean their teeth, and even if they do, they often do not use dental materials.…”
Section: Discussionsupporting
confidence: 92%
“…However, the results are not in agreement with various other studies. In certain studies, there was a predominance of males over females [ 73 , 74 , 75 ], and in other studies, females over the males [ 46 , 76 ]. Thus, it is interfered that the difference in sex is not an important matter for dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their earlier study showed a male preponderance, however, in this study, females were affected more [28]. Bhuiyan et al reported that primary school children have limited awareness about oral health and poor knowledge of oral hygiene habits and it creates muchneeded niche for implementing school-based oral health awareness and education programs [29]. This is also supported by other studies in Bangladesh [30][31][32].…”
Section: Discussionsupporting
confidence: 73%
“…7). In another study, 26 most children brushed in the morning, before or after their first meal, while only 8% brushed at night as well before bedtime. One hundred five (71.4%) of the children were used to clean their teeth.…”
Section: Resultsmentioning
confidence: 90%